DAPATKAH MODEL BLENDED LEARNING MEMPENGARUHI KEMANDIRIAN BELAJAR MATEMATIKA SISWA? - Budi Yanto; Heri Retnawati (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2018)
This study aims to determine the effect of blended learning models to self-regulated learning of mathematics in eight-grade student in West Lampung. This study uses a quasi-experimental design with a population of all eighth-grade students of SMP Negeri 1 Way Tenong. Classes are randomly selected and treated with blended learning models. The instrument used is a self-regulated learning questionnaire. The results of this study indicate that blended learning models can improve self-regulated learning of mathematics.